Climate change-induced conflicts in Southeast Nigeria and urban food security: Implication to urban sustainability and sustainable development - Okafor, Samuel O.; Onah, Sebastian Okechukwu; Abah, George O.; Oranu, Chizoba O. (TeMA - Journal of Land Use, Mobility and Environment, 2023)
<span class="NormalTextRun SCXW219321352 BCX0" data-ccp-parastyle="Abstract" data-ccp-parastyle-defn="{"ObjectId":"1bd0699c-d05b-40ee-a50e-d33dfe8f7ae9|223","ClassId":1073872969,"Properties":[469775450,"Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"Abstract",335572020,"1",201342448,"1",469777841,"Tahoma",469777842,"Tahoma",469777843,"Calibri",469777844,"Tahoma",469769226,"Tahoma,Calibri",268442635,"18",335551547,"1033",335559740,"276",201341983,"0",335559739,"0",335551550,"6",335551620,"6",469778324,"Normal"]}">Climate change is multifaceted and complex in its impacts on the human population across the globe. The areas of impacts include food insecurity and urban sustainability issues, which are currently ravaging the developing nations where sustainability policy frameworks are lacking or in passivity. The complex impacts of climate change on the urban population have been explored by some researchers in other regions of the world however, the nexus between climate change-induced conflicts and urban food insecurity and sustainability crises is yet to be empirically explored especially in the developing nations such as in sub-Saharan Africa. The aforementioned research and policy problem was the drive to the present study. The study which was guided by sustainability and climate change models, involved 1,658 respondents among the farming communities in southeast Nigeria using survey design and questionnaire as data gathering instrument. The study concludes that there is a cycle of anthropogenic activities among the urban population contributing to climate change, and climate change crises returning to urban population in form of food security and urban sustainability crises due to weak and passive environmental sustainability policy framework in Nigeria.